Numerical modeling of concrete cracking - Hofstetter, Günter; Meschke, Günthe; SpringerLink (Online service). (Wien New York Springer, 2011)
The book presents the underlying theories of the different approaches for modeling cracking of concrete and provides a critical survey of the state-of-the-art in computational concrete mechanics. It covers a broad spectrum of topics related to modeling of cracks, including continuum-based and discrete crack models, meso-scale models, advanced discretization strategies to capture evolving cracks based on the concept of finite elements with embedded discontinuities and on the extended finite element method,  and extensions to coupled problems such a hygro-mechanical problems as required in computational durability analyses of concrete structures.
Electronic reproduction.
Keywords: Concrete -- Cracking -- Mathematical models; Reinforced concrete -- Cracking -- Mathematical models; Electronic books